Safety and health of professional drivers who drive on Brazilian highways - Fernanda Veruska Narciso; Marco Túlio de Mello
ABSTRACT Traffic accidents and resulting injuries and deaths have become a global epidemic. In Brazil, most professional drivers, especially truck drivers, face irregular working hours and can be awake for more than 18 hours/day, which reduces their performance and alertness. In this article, we discuss the laws related to Brazilian professional drivers and their current amendments (No. 12,619/2012 and No. 13,103/2015) in relation to working hours at the wheel and rest breaks, which are vital for the quality of life of drivers and society in general. We note that the new law appears to be less efficient than the previous one as it causes insecurity and concern to the users of the transportation system, drivers, and employers. To restrict and reduce accidents, deaths, and injuries in traffic, appropriate legislation is essential, aiming at the safety of workers and users of highways. The law must also benefit the commercial aspect, strengthening the reduction in production and logistics losses. Additionally, traffic education programs are needed, as well as better supervision in relation to total working hours.